Novel role for non-invasive neuromodulation techniques in central respiratory dysfunction - Lv, Lan; Cheng, Xiaoping; Yang, Jiaying; Chen, Xinyuan; Ni, Jun (Frontiers in Neuroscience, 2023)
Respiration is a crucial steady-state function of human life. Central nervous system injury can damage the central respiratory pattern generator (CRPG) or interrupt its outflow, leading to central respiratory paralysis and dysfunction, which can endanger the patient's life. At present, there is no effective means to reverse this process. Commonly used non-invasive neuromodulation techniques include repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS) and so forth, which have been widely applied in nervous system diseases and their various secondary symptoms, but rarely in respiratory function. Clinical and animal studies have confirmed that TMS is also suitable for investigating the excitability and plasticity of ascending corticospinal respiratory pathways. In addition, although rTMS and tDCS differ in their respective mechanisms, both can regulate respiratory networks in healthy individuals and in diseased states. In this review, we provide an overview of the physiology of respiration, the use of TMS to assess the excitability of corticophrenic pathways in healthy individuals and in central respiratory disorders, followed by an overview of the animal and clinical studies of rTMS, tDCS and so forth in regulating respiratory circuits and the possible mechanisms behind them. It was found that the supplementary motor area (SMA) and the phrenic motor neuron (PMN) may be key regulatory areas. Finally, the challenges and future research directions of neuroregulation in respiratory function are proposed. Through understanding how neuromodulation affects the respiratory neural circuit non-invasively, we can further explore the therapeutic potential of this neuromodulation strategy, so as to promote the recovery of respiratory function after central nervous system diseases or injury.